MODERN APPROACHES TO THE EARLY DIAGNOSTICS OF CARDIOVASCULAR DISORDERS IN CHILDREN WITH SUBCLINICAL HYPOTHYREOSIS - Павликівська, Б. М.; Юрцева, А. П.; Ткач, Б. Н. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents data on methods for early diagnostics of cardiovascular disorders in children with subclinical hypothyreosis. The violation of physical development, energy equipment, pro- and antioxidant defense in children with subclinical hypothyreosis is set. The study of energy metabolism, pro- and antioxidant systems may be used in early diagnostics of cardiovascular disorders and enerhodefitsytu as well – with the aim of explanation drugs enerhotropic and metabolic actions in complex treatment and reabilitation of children with SH.